Ambient PM2.5 exposure and expected premature mortality to 2100 in India under climate change scenarios - Sourangsu Chowdhury (Nature Portfolio, 2018)
Modulation of ambient PM2.5 exposure and premature mortality burden in India under climate change scenarios is unclear. Here the authors show that the premature mortality burden is projected to decrease in 2100 relative to present day under all possible combined climate change and socioeconomic pathways scenarios.